Pengaruh Gaya Kepemimpinan Situasional Dan Kompensasi Kerja Terhadap Efektivitas Kerja Dengan Motivasi Kerja Sebagai Variabel Intervening Pada Pejabat Fungsional Statistisi Badan Pusat Statistik Provinsi Daerah Istimewa Yogyakarta - Suparno, Suparno; Haryono, Siswoyo (Jurnal Manajemen Bisnis, 2015)
This study conducted to examine and analyze the effect of situational leadership styles and job compensation on job efectiveness, with job motivation as a mediating variable.The object of this study is the office of the Statistics of Yogyakarta  province, and the subject of this study are official statisticians  in the Statistics of Yogyakarta Province. The sampling technique in this study using a sample saturated. All official statisticians, who is not studying and leave, in Statistics of Yogyakarta  province totaling 92 people are given a questionnaire study.Data from the study were tested and analyzed using the Smart-PLS. The first conclusion is situational leadership styles  positive and  significantly  influence job motivation. The second conclusion is job compensation positive and significantly influence job motivation. The third conclusion is situational leadership styles  positive  but not significantly  influence job efectiveness. The fourth conclusion is job compensation  positive and significantly  influence job efectiveness. The fifth conclusion is job motivation positive and significantly  influence job efectiveness. The study also concluded that situational leadership styles  influence job efectiveness  on official statisticians  of the Statistics of Yogyakarta  province , with job motivation as a mediating variable.